Odpowiedzialność cywilna za szkody wyrządzone przez bezzałogowe statki powietrzne w świetle nowelizacji ustawy Prawo lotnicze - Pykało, Julia (Studia Prawa Publicznego, 2026)
The article presents the current model of civil liability for damage caused by unmanned aerial vehicles in light of the amendment to the Aviation Law. The dynamic development of unmanned aerial vehicle technology has made drones a common tool used both recreationally and commercially. With their increasing availability and increased use, there has emerged a need for comprehensive regulation of liability for damage to persons and property. The amendment to the Aviation Law, introducing mandatory third-party liability insurance for operators of drones weighing between 250 g and 20 kg, represents a significant step towards streamlining and standardizing the system. These changes also align with the broader trend of adapting regulations to the rapidly evolving drone market, the increasing number of applications for these devices, and the evolving U-Space concept. This regulation has filled a previous legal gap, creating a mechanism for protecting injured parties. This article presents the development of unmanned aerial vehicles over the years and the current principles of civil liability for damage caused by such vehicles. The basic categories of drone operations and classifications, which determine the scope of user responsibilities, are also discussed. Additionally, part of the paper is devoted to the amendment’s implications, including how the new regulations impact safety, the effectiveness of law enforcement, and the effective protection of injured parties. An attempt is also made to assess the minimum amount of insurance and its proportionality to potential hazards.